1983
DOI: 10.1111/j.1095-8649.1983.tb02891.x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of cortisol to brown trout, Salmo trutta L., and its effects on the susceptibility to Saprolegnia infection and furunculosis

Abstract: Oral administration and intraperitoneal implantation can be used to administer cortisol to the brown trout. Both techniques produce a dose-dependent increase in plasma cortisol concentration and the experimental procedures reduce the stress response in control fish to a minimum level. The plasma levels of the steroid are within the physiological range for the fish and the time of the response to acute oral administration is similar to that for such stresses as crowding, pollution and confinement. The evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
2
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(114 citation statements)
references
References 31 publications
(27 reference statements)
9
102
2
1
Order By: Relevance
“…-150 spores 1-') and in providing a sustained, though declining, challenge for a period of 10 to 14 d. However, we were unable to infect rainbow trout by exposure to the spore challenge without first predisposing the fish to infection by elevating blood cortisol levels using slow-release cortisol implants; shamimplanted control fish did not exhibit evidence of colonisation by Saprolegnia parasitica. Carballo et al (1995), although employing more invasive techniques than in the present study, also reported that elevated blood cortisol levels were a major factor in successfully inoculating rainbow trout with S. parasitica, and it is well-established that cortisol-implanted salrnonids display an increased susceptibility to infection by the 'natural' Saprolegnia spore challenge (Pickering & Duston 1983, Pickering & Pottinger 1989. Rainbow trout clearly have a very effective protective mechanism preventing the successful attachment and germination of S. parasitica spores which is compromised by cortisol adrninistration, allowing S. parasitica to act as a primary pathogen.…”
Section: The Disease Modelsupporting
confidence: 48%
“…-150 spores 1-') and in providing a sustained, though declining, challenge for a period of 10 to 14 d. However, we were unable to infect rainbow trout by exposure to the spore challenge without first predisposing the fish to infection by elevating blood cortisol levels using slow-release cortisol implants; shamimplanted control fish did not exhibit evidence of colonisation by Saprolegnia parasitica. Carballo et al (1995), although employing more invasive techniques than in the present study, also reported that elevated blood cortisol levels were a major factor in successfully inoculating rainbow trout with S. parasitica, and it is well-established that cortisol-implanted salrnonids display an increased susceptibility to infection by the 'natural' Saprolegnia spore challenge (Pickering & Duston 1983, Pickering & Pottinger 1989. Rainbow trout clearly have a very effective protective mechanism preventing the successful attachment and germination of S. parasitica spores which is compromised by cortisol adrninistration, allowing S. parasitica to act as a primary pathogen.…”
Section: The Disease Modelsupporting
confidence: 48%
“…Scale bar = 30 unl cortisol g-' body wt which has been demonstrated to elevate blood cortisol levels and cause chronic imrnunosuppression in coho salmon (Maule et al 1987). Levels of 0.5 mg cortisol g.' body wt and less have also been demonstrated to cause chronic immunosuppression of both rainbow Oncorhynchus mykiss and brown trout Salmo trutta (Pickering & Duston 1983, Pickering & Pottinger 1985, Kent & Hedrick 1987. Woo et al 1987.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting similarity is that only the skin of infected fish that developed disease became colonized by streptococci, while the skin of uninfected fish and fish infected at sublethal doses remained uncolonized. Fish respond to stress by increasing levels of cortisol in serum (43,57), which can induce a profound immunosuppression (22,43,46,67). A serious infection resulting in damage to tissue would likely induce this response, which may depress a defense critical for controlling bacterial colonization on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…A serious infection resulting in damage to tissue would likely induce this response, which may depress a defense critical for controlling bacterial colonization on the skin. Fish in aquaculture become most susceptible to S. iniae infection under conditions of stress (46), including overcrowding, improper temperature, overfeeding, and poor water quality. In preliminary experiments, infection by exposure to streptococci in water was possible when the zebrafish were housed for short periods of time under conditions which mimicked aspects of a stressful aquaculture environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation